POZIOM A
d) (6c + 1)(c - 1) = 6c² - 6c + 1c - 1 = 6c² - 5c - 1
e) (4 - d)(2d + 2) = 8d + 8 - 2d² - 2d = 6d + 8 - 2d²
f) (5 - n)(n+3) = 5n + 15 - n² - 3n = 2n - n² + 15
POZIOM B
d) (2a - b)(a - 2b) = 2a² - 4ab - ab + 2b² = 2a² - 5ab + 2b²
e) (m - n)(n - m) = mn - m² - n² + mn = 2mn - m² - n²
f) (-2a + k)(2k + 3a) = -4ak - 6a² + 2k² + 3ak = -ak -6a² + 2k²
POZIOM C
d) 2(x + y) - (1 - 2x)(1 + 2y) = 2x + 2y - (1 + 2y - 2x - 4xy) = 2x + 2y - 1 - 2y + 2x + 4xy = 4x - 1 + 4xy
e) (4a - 1)(2b + 2) + 2b(1 - 2a) = 8ab + 8a - 2b - 2 +2b - 4ab = 4ab - 2 + 8a
f) (2a + b)(a - 1) - (b - 1)(a + 2) = 2a² - 2a + ab - b - (ab + 2b - 1a - 2) = 2a² - 2a + ab - b - ab - 2b + 1a + 2 = 2a² - a - 3b + 2